2007
DOI: 10.2320/matertrans.mj200727
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Zr-Cu Base Metallic Glasses by means of Hydrogen Internal Friction Peak

Abstract: The hydrogen internal friction peak in Zr 50 -metallic glasses (Zr 50 Cu 50 , Zr 50 Cu 40 Al 10 and Zr 50 Cu 35 Al 10 Ni 5 ) was studied. The hydrogen internal friction peak was shifted exponentially to lower temperatures with increasing hydrogen concentration similarly to other Zr-Cu base metallic glasses reported in the literature. The peak height increased in proportion to the square-root of hydrogen concentration. These results were discussed in the view point of the hydrogen induced structural relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…6 in [6] too). The 135 K peak is much broader than a single relaxation peak, suggesting that the outline of the low-temperature internal friction is indicative of the strength of the constituent relaxations as suggested for the hydrogen internal friction in amorphous (a-) alloys [12]. That is, the hydrogen Fig.…”
Section: Resultsmentioning
confidence: 86%
“…6 in [6] too). The 135 K peak is much broader than a single relaxation peak, suggesting that the outline of the low-temperature internal friction is indicative of the strength of the constituent relaxations as suggested for the hydrogen internal friction in amorphous (a-) alloys [12]. That is, the hydrogen Fig.…”
Section: Resultsmentioning
confidence: 86%
“…31) On the other hand, it was reported that hydrogens in the amorphous alloys induced a large internal friction peak below room temperature. 32) The effect of He on nanocrystallization is reversible under the He pressure as shown in Fig. 4.…”
Section: Electropulsing By Changing the Atmosphere Frommentioning
confidence: 95%
“…They proposed a sequential filling by hydrogen atoms of pre-existing sites of different energies, for Zr-Ni alloys the sequence of site filling is Zr 4 then Zr 3 Ni then Zr 2 Ni 2 and so on. Nevertheless, several authors reported experimental measurements that are incompatible with a "static" random-alloy model [20][21][22][23]. They underlined that the initial atomic configuration of the amorphous alloy is not frozen and can evolve in the presence of hydrogen.…”
Section: Introductionmentioning
confidence: 92%